“This Is a New Thing in the World”: Design and Discontent in the Making of a “Garage Lab” - Scroggins, Michael J. (2017)
This dissertation draws on twenty-four months of fieldwork at Biocurious, a "garage lab" in Silicon Valley expressly designed to democratize science, and a self-described "new thing in the world." From that starting point, this dissertation poses the following questions: a) how does a "garage lab" come to be recognized as a "garage lab," and b) what kind of scientist works to what effect inside a "garage lab." These questions are taken up on two levels: theoretically through a critical engagement with anthropological approaches to design, an explication of the difficulties and paradoxes inherent in the relationship between expertise and democracy, and through the business of producing an audience for and presenting "new things in the world" to the public, also found in precursors such as Thomas Edison and P.T. Barnum. Empirically, these questions are taken up as a particular problem for a group of people in Silicon Valley as they go about the everyday work of making a "garage lab" and deliberating among themselves and their consociates over its perils and possibilities. Ethnographically, this dissertation is animated by my participation initially as a volunteer, then as a member of the "garage lab," and finally through my participation as a member of a community project at Biocurious. Theoretically, this dissertation furthers Flusser's (1999) theory of design as "a trick against nature [the given]" by pulling it tight to the traditional anthropological concern with cultural production and critically examines the claim to democratization, finding the claim to democratization at Biocurious a reordering rather than erasing the hierarchy of expertise. Finally, the dissertation considers the afterlife of "new things in the world," which fade into the background as they inevitably move from the made (cultured) to the given (natural) Following the text are two appendixes. Appendix One addresses the folklore of the modern laboratory by examining instructional stories told at the "garage lab," the unicorn in Silicon Valley, and the signs of domestic life in the "garage lab." Appendix Two constitutes notes towards a mechanical model that can account for the life of "new things in the world," as they inevitably form for the basis for further cultural productions.